Deep Neck Space Abscesses; a Study of 51 Cases at Al-Thowra Hospital in El-Beyda City, Libya - Khaled Hassen; Ahmed Alobedy; Sana Gheth; Marfoua Ali (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The aim of this investigation was to identify the clinical outcomes, risk factors, and management strategies of deep neck abscesses (DNAs) at Al-Thowra hospital in El-Beyda City. Methods. This study was conducted on 51 patients diagnosed with DNAs, from January 2020 to October 2021 at the Department of Otolaryngology, in Al-Thowra hospital in El-Beyda City. Results. This study showed that males are most likely to have DNAs, the majority of patients were in the 16-30- and 0-15-year age groups. Fever and dysphagia were the most common symptom identified with 76.47 % and 74.51 % patients respectively. Tonsillopharyngitis and Odontogenic infection with 45.10 % and 31.37 % respectively were the most common etiological factor. Peritonsillar abscess 47.06 % was the common site of presentation. Surgical intervention incision and drainage was carried out in 39 patients (76.47 %). Conclusion. Odontogenic infections were the most common etiological factor for DNAs. Close attention must be paid to the management of patients with deep neck infections, especially children’s patients. The surgical incision and drainage remain the main method of treating DNAs.